2010
DOI: 10.1016/j.jfoodeng.2009.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Water vapor and oxygen-barrier performance of corn–zein coated polypropylene films

Abstract: a b s t r a c tA novel corn-zein coating structure on polypropylene (PP) films was developed to examine its feasibility as an alternative water vapor and oxygen-barrier for flexible packaging industry. The barrier properties of the resulting films were evaluated as affected by coating formulation (solvent, corn-zein, plasticizer concentration and plasticizer type). Corn-zein with different amounts (5% and 15%) was dissolved in 70% and 95% aqueous ethanol solution at 50°C, respectively. Solutions of corn-zein p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 23 publications
6
68
1
2
Order By: Relevance
“…Transport properties of coated packaging materials are affected by coating composition (Tihminlioglu et al 2010). Therefore, the detailed study of the water-vaporbarrier properties of the HPMC-coated papers as influenced by coating composition is of great importance for practical and commercial purposes.…”
Section: Water Vapor Permeability (Wvp)mentioning
confidence: 99%
“…Transport properties of coated packaging materials are affected by coating composition (Tihminlioglu et al 2010). Therefore, the detailed study of the water-vaporbarrier properties of the HPMC-coated papers as influenced by coating composition is of great importance for practical and commercial purposes.…”
Section: Water Vapor Permeability (Wvp)mentioning
confidence: 99%
“…The most common quality losses are associated with water vapor and oxygen transfer [1]. The research of barrier properties is very important from a technological point of view [2][3].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tihminlioglu et al (2010) investigated zeincoating polypropylene films and found significant improvements in WVP and oxygen barrier properties. However, zein has been found to be incompatible with natural polymers such as 28 starch and gelatin and synthetic polymers such as poly ε-caprolactone (reviewed by Sessa et al 2011).…”
Section: Blending With Synthetic Polymers or Other Natural Polymersmentioning
confidence: 99%